Measuring the performance of emerging businesses: A validation study - Chandler, Gaylen N.; Hanks, Steven H. (Journal of Business Venturing, 1993)
To identify and substantiate the correlates and antecedents of new venture performance, it is requisite to identify the most relevant performance dimensions and move toward the use of common measures of performance. Relevant, reliable, and valid measures of new venture performance are essential to explore vital relationships between independent variables and venture success and develop sound venture performance theory. In this paper we discuss three of the most common measurement approaches used in new venture performance research when only self-report data are available, and present a comparison of these approaches: (1) measuring firm performance in broadly defined categories, (2) the use of subjective measures of executive or owner satisfaction with firm performance, and (3) the use of subjective measures of firm performance relative to competitors. After discussing the relevance and potential benefits and drawbacks of each approach we use empirical data to examine and compare the availability, reliability, and relative validity of measures developed using these approaches. The sample consisted of manufacturing businesses (SIC codes 20–39) started or reorganized in the corporate form between 1980 and 1991 in nine counties in northwestern Pennsylvania's identified by a major marketing research service. Questionnaires were returned by primary respondents in 120 companies; complete matching firm performance data from a second respondent were returned for 45 of the firms. The pattern of results favors the use of two dimensions of venture performance: growth and business volume. The growth and business volume measures operationalized in this research have good availability and internal consistency and are superior to the satisfaction with performance and performance relative to competitors' scales in terms of content validity. Evidence of the external validity of the measures is provided by regression analysis showing independent variables identified and substantiated by previous research to be related to performance in the hypothesized manner. The satisfaction with performance index had a high disclosure rate, strong internal consistency, and relatively strong inter-rater reliability. There is little evidence supporting its external validity. With the exception of its negative relationship with the level of competition, none of the predicted relationships are substantiated. The performance relative to competitors' disclosure rate was somewhat lower as was the inter-rater reliability; however, it emerged as a strong independent construct with a high level of internal consistency. There was evidence for the external validity of this measure. The independent variables related to the performance relative to competitors' index are similar to those related to both the growth and business volume dimensions as predicted from previous theoretical work and research findings. In summary, this research makes several contributions to the new venture performance literature. First, when researchers are required to use self-reported measures of venture performance, growth and business volume are the dimensions of performance most familiar to and most commonly referenced by the founders. Second, it provides additional evidence for the accuracy and reliability of founder reported performance data. Third, it provides examples of specific measures with evidence that supports their relevance, availability, reliability, and validity. We believe this research can provide a base for future venture performance research. We hope that these findings will be used to help better our understanding of the dynamics impacting new venture performance and lead to improved managerial practice in emerging firms.